Project-Based Learning Podcast as Pedagogical Design: A Case Study of Student Speaking Learning - Agus Darmuki; Nur Alfin Hidayati; Alfredo M. Esteban Jr. (Jurnal Sastra Indonesia, 2026)
Speaking Learning In Higher Education Is Often Trapped In Final-Product Assessments And Minimal Contextual Exercises, Resulting In An Imbalance In Fluency, Diction And Accuracy, Organization Of Ideas, And Audience Sensitivity. The Purpose Of This Study Is To Describe A Project-Based Learning Podcast Model As A Pedagogical Design To Strengthen Authentic, Reflective, And Digitally Relevant Speaking Skills. This Study Used A Mixed Methods Approach With A Case Study Design. This Research Was Conducted At The Indonesian Language And Literature Education Study Program, Muria Kudus University. The Results Showed That Project-Based Podcasts, Using Editable Pretest-Posttest Data From 32 Students, Showed An Increase In The Average Speaking Score From 67.96 To 79.83, A Statistically Significant Increase. The Qualitative Section Utilized Observation Notes, Student Reflections, And Short Interview Excerpts That Demonstrated Improvements In Confidence, Fluency, Audience Awareness, And Revision Discipline, While Also Highlighting Challenges In Vocal Performance, Time Management, And Audio Editing. The Findings Suggest That Project-Based Podcasts Hold Pedagogical Promise Because They Expand Speaking Practice From One-Off Classroom Performances To Repeated, Audience-Oriented, And Documented Oral Productions. The implication is that Project-Based Learning podcasts are worthy of being positioned as an innovative pedagogical design for speaking instruction in higher education because they can present authentic, collaborative, and student-centered language practices.